2020
DOI: 10.3390/ijms21030855
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Surface Expression of Intercellular Adhesion Molecule 3, the Induction of Apoptosis, and the Inhibition of Cell-Cycle Progression of Human Multidrug-Resistant Jurkat/A4 Cells Exposed to a Random Positioning Machine

Abstract: Experiments from flight- and ground-based model systems suggest that unexpected alterations of the human lymphoblastoid cell line Jurkat, as well as effects on cell growth, metabolism, and apoptosis, can occur in altered gravity conditions. Using a desktop random positioning machine (RPM), we investigated the effects of simulated microgravity on Jurkat cells and their multidrug-resistant subline, Jurkat/A4 cells. The viability of Jurkat/A4 cells decreased after simulated microgravity in contrast with the Jurka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Furthermore, conditions of real and simulated microgravity can influence cell survival and increase the amount of apoptosis in different cell types and tissues (Zhao et al, 2018;Jiang et al, 2020;Mao et al, 2020;Pan et al, 2020;Sokolovskaya et al, 2020). The conquest of space is very important to us humans.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, conditions of real and simulated microgravity can influence cell survival and increase the amount of apoptosis in different cell types and tissues (Zhao et al, 2018;Jiang et al, 2020;Mao et al, 2020;Pan et al, 2020;Sokolovskaya et al, 2020). The conquest of space is very important to us humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when screening targeted drugs, the selection of cell model that responds to simulated microgravity is also critical. It was reported that, compared with parental Jurkat cell line, the Jurkat/A4 cells are more sensitive to simulated microgravity with the changes of adhesion molecule ICAM-3 expression and cell morphology [113]. Therefore, Jurkat/A4 cells are useful models for studying microgravity effects and testing anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of 1 × 10 6 cells were suspended in 100 µL binding buffer containing fluorescein isothiocyanate (FITC)-conjugated Annexin V and propidium iodide (PI). After incubation in the dark and on ice for 15 min, cells were analyzed using a flow cytometer (Beckman Coulter, CA, USA) [ 76 ]. The cell cycle proportion of HBMECs was carried out using flow cytometric analysis as described previously.…”
Section: Methodsmentioning
confidence: 99%